THE ASSOCIATION BETWEEN INTRACARDIAC HEMODYNAMICS AND LUNG FUNCTION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - N. V. Vysotskaya; V. V. Lee; N. Yu. Timofeeva; V. S. Zadionchenko; T. V. Adasheva (Архивъ внутренней медицины)
Study objective. To assess the association between intracardiac hemodynamics and airway obstruction with pulmonary hyperinflation in patients with chronic obstructive pulmonary disease.Materials and methods. Ninety-six patients with chronic obstructive pulmonary disease, aged 40 to 75 years, without concomitant cardiovascular disease, were examined and divided into 4 groups according to the severity of the disease. The patients underwent general clinical examination, spirometry, 24-hour pulse oximetry and echocardiography with assessment of linear and volumetric parameters, as well as diastolic function of left and right ventricles.Results. Linear and volumetric parameters of the left ventricle, LV myocardial mass and geometry in the examined patients with chronic obstructive pulmonary disease matched threshold values. The progression of the severity of chronic obstructive pulmonary disease was accompanied by decrease of the end-diastolic size of the left ventricle, ratio of peak early to late diastolic filling velocity for the left ventricle (E/A) without significant changes in the left ventricle isovolumetric relaxation time (IVRT). Moderate correlations of the inspiratory capacity with the end-diastolic size of the left ventricle (r=0.612; p=0.001) and the left ventricle E/A (r=0.464; p=0.001); forced expiratory volume in 1 second (FEV1) with the left ventricle E/A (r=0.600; p=0.011) were established. As a result of the logistic regression performed, the predictor value of the inspiratory capacity was confirmed (Wald χ2 — 5.795; р=0.024). Impairment of left ventricular diastolic function of grade I was revealed in 12 (31.6 %) patients in group 2, in 7 (24.1 %) patients in group 3, and in 9 (56.2 %) patients in group 4.Conclusion. Airway obstruction severity and pulmonary hyperinflation progression in patients with chronic obstructive pulmonary disease and without concomitant cardiovascular disease is associated with a decrease of left ventricular size and diastolic filling, contributes to the development of the left ventricular diastolic dysfunction, predominantly due to the decrease in filling velocity parameters.